EFFECTIVENESS OF SNAKES AND LADDERS MEDIA ON MENARCHE KNOWLEDGE IN STUDENTS - Nurwijaya, Nita; Nuraeni, Neni; Gunawan, Indra (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2024)
Women are said to be puberty when they have experienced menarche, which is the first menstruation that occurs at the age of 10-16 years. Menarche for some teenagers are scary, anxious, stressful, and emotional and even depressed things, some even refuse if it’s coming. This is because the lack of understanding and readiness in dealing with menarche due to lack of information about menarche in their ages. One of the efforts is to provide information through counselling by using innovative media that is appropriate for adolescents in elementary school, because children at this age are prefer to play in groups with peers, the snake and ladder game is chosen. The purpose is to knowing the effectiveness of snakes and ladders media on knowledge about menarche in female students at SDN Sindanggalih Tasikmalaya City. Quantitative research method with Quasy-experiment pre-test and post-test approach without control group design were used in this research. A sample of 18 respondents who had never menstruated. The questionnaire as a data collector is the same between pretest and pos test. This study began with a pretest for 20 minutes then a 5-minute break. Followed by a game of snakes and ladders with the topic of menarche. Next, a post-test is carried out for 20 minutes after resting for 20 minutes. The data was analysed by using paired T test. The results obtained an average knowledge value before the intervention of 9.39, a standard deviation of 2.873, a low of 7.96 and a high of 10.82 at a CI of 95%, while after the intervention of 11.00, a standard deviation of 1.534, a low of 10.24 and a high of 11.76 at a CI of 95%. The results of the t-paired test show a value of ρ 0.00. The conclusion of the snakes and ladders media is effective for knowledge about menarche in female students at SDN Sindanggalih Tasikmalaya City. Advice for researching about the attitude of female students in the game of snakes and ladders about menarche.